1996
DOI: 10.1109/77.559340
|View full text |Cite
|
Sign up to set email alerts
|

3.5 GHz operation of a superconducting packet switch element

Abstract: The paper introduces a prototype model of a superconducting packet switch which is composed of an input buffer, a contention solver, and a distribution network. The input buffer and the contention solver enable contention-free distribution of data packets. The total design of the prototype has been completed and the total operation has been numerically simulated and confirmed.A 2 2 2 switching element which controls the paths of two packets is the key component of the prototype. The basic switching element wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The most representative results of the logic application area are switching circuits using Josephson junction Hosoya et al reported on the design and test of a prototype superconducting packet switch [11,34]. Figure 1 shows a block diagram of the prototype.…”
Section: Logic Circuit Applicationsmentioning
confidence: 99%
“…The most representative results of the logic application area are switching circuits using Josephson junction Hosoya et al reported on the design and test of a prototype superconducting packet switch [11,34]. Figure 1 shows a block diagram of the prototype.…”
Section: Logic Circuit Applicationsmentioning
confidence: 99%
“…Latch-type ac-powered gates, which are the concern of this paper, have been shown to operate at several gigahertz [3], [4]. However, full demonstrations of multi-gigahertz operaManuscript received Aug 20, 1996.…”
Section: Introductionmentioning
confidence: 99%